Analisis Produksi Sagu (Studi Kasus di Desa Hatunuru Kecamatan Taniwel Timur Kabupaten Seram Bagian Barat) - Siahaya, Troice E; Sahureka, Mersiana; Seite, Damaris (Universitas Pattimura, 2021)
Sago trees, especially sago flour, have a high economic value. Various snacks made from sago flour are used as local foods such as sago tumang, papeda, and different cakes. This study aims to find out the economic value of sago production. Data collection method using interviews and direct surveys of 6 key informants who process sago. Primary and secondary data are analyzed qualitatively and quantitatively. The results showed that sago trees have economic value. The result of calculating the monetary value for the roof is ± Rp 304,660,000, sago tumang amounted to ± Rp 55,987,750 to ± Rp 68,808,250, and sago plate amounted to ± Rp 14,030,000 per year so that the total economic value of sago production of Rp 785,160,000 / year. Sago contributes to the economic improvement of the community and is a culture that is as a local food of the Moluccas that must continue to be preserved.